Parametric studies on the dynamic properties of stay cables interconnected with uniformly distributed cross-ties. Issue 4 (March 2019) - He, Xuhui; Peng, Yihua; Jing, Haiquan; Zhou, Lei; Zhou, Yu
The cable-stayed bridge is one of the most popular super-long-span bridges. However, the stay cables are prone to large vibration because their inherent characteristics of low mass, small damping, and large flexibility. Keeping the stay cables calm is significant to ensure their safety. Over the past decade, the use of cross-tie has become a practical and effective method to suppress the cable vibrations. Extensive research has led to a better understanding of the mechanics of cable-cross-tie systems and revealed that the application of a single or a few cross-ties may yield a potential deficiency in local modal vibrations. Recently, the use of large numbers of small elastic cross-ties uniformly distributed along stay cables has been proposed to replace the single or multiple cross-ties traditionally used to suppress the large vibrations of stay cables and delay the "mode localization." In a previous study, the closed-form solutions to the free vibration of two equal-length cables with uniformly distributed elastic cross-ties have been derived and a numerical procedure has been developed to calculate the resulting modal frequencies and mode shapes. The uniformly distributed cross-ties successfully delayed the "model localization." In the present study, the effects of the stiffness, width, and location of the uniformly distributed cross-ties on the free vibration of the general cable-cross-tie system are further investigated through parametric analyses. The results indicate that the stiffness and width of the cross-ties significantly affect the modal frequencies and mode shapes of the cable cross-tie system, while the location of the cross-ties has a relatively small effect.